1999
DOI: 10.1002/qj.49712556015
|View full text |Cite
|
Sign up to set email alerts
|

Cloud‐to‐ground lightning activity and radar observations of storms in the pyrénées range area

Abstract: This paper analyses radar observations and cloud-to-ground (CG) lightning flash activity of several thunderstorms occurring over the Pyr6nks range during the night of 23-24 August 1993 and the afternoon of 24 August 1993. The available data consisted of the European meteorological bulletin, the plan position indicator radar scans at three elevations performed by the 5.5 cm wavelength Rodin radar of Toulouse, and the characteristics of the CG lightning strikes.The first thunderclouds began to develop at around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The geographical location of the Pyrenees and the Ebro Valley is indicated in Figure 1. The Pyrenees are one of the areas in Europe with the highest lightning frequency (Molinie et al, 1999;Pineda et al, 2010;Anderson and Klugmann, 2014) and is a good place to distinguish the LNO x signal due to its remoteness and very low NO x background (Vinken et al, 2014). Airflows over the studied areas are influenced by the proximity of the Mediterranean Sea and the Atlantic Ocean, the high mountains of the Pyrenees, cold fronts cossing Europe, and thermal low centered over the Iberian Peninsula (Pineda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The geographical location of the Pyrenees and the Ebro Valley is indicated in Figure 1. The Pyrenees are one of the areas in Europe with the highest lightning frequency (Molinie et al, 1999;Pineda et al, 2010;Anderson and Klugmann, 2014) and is a good place to distinguish the LNO x signal due to its remoteness and very low NO x background (Vinken et al, 2014). Airflows over the studied areas are influenced by the proximity of the Mediterranean Sea and the Atlantic Ocean, the high mountains of the Pyrenees, cold fronts cossing Europe, and thermal low centered over the Iberian Peninsula (Pineda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They occur in low wind shear environments, typically last one hour, and have a marked diurnal cycle with a maximum of occurrence in the late afternoon (Chappell 1987;S. Coquillat and E. Defer 2010, personal communication;Oriol 2008;Dai 2001;Dai et al 1999;Molinié et al 1999).…”
Section: Maximum Rainfall Intensitymentioning
confidence: 96%
“…Kempf and Krider () presented a compilation of RLR values including some obtained from other works, and found values ranging from 38 to 72 × 10 6 kg per flash for isolated thunderstorms in Florida, Spain and France, and values as high as 5000 × 10 6 kg per flash for mesoscale thunderstorms in Australia and Central United States. Molinie et al () found values as low as 3 × 10 6 kg per flash for the Pyrenees, while Williams et al () found values up to 500 × 10 6 kg per flash for Australia.…”
Section: Introductionmentioning
confidence: 99%